Cross sectional analysis looking at the disease profile of patients requiring tracheotomies by the otorhinolaryngology department at a tertiary care centre - Geyser, Amelia (My University, 2018)
Background: Tracheotomy is an important lifesaving surgical procedure and plays a prominent role in developing countries where patients may present with advanced airway obstruction very late.(1) The world has seen a paradigm shift in the indication for tracheotomy from mainly short-term procedures for upper airway obstruction to long-term uses for chronic disease and prolonged ventilation.(2) Aim: Doing an audit on tracheotomies performed in a tertiary referral centre in a third world country and comparing it to available literature. Method: A retrospective review was done in the Ear, Nose and Throat (ENT) Department at the Chris Hani Baragwanath Academic Hospital over a 4 year period from January 2012 to December 2016. Medical records of 269 tracheotomised patients were reviewed, and the data collected included age, gender, indication and diagnosis. Patients were then categorised according to indication for tracheotomy and different age groupings. The data was analysed using standard statistical methods. Results: Two hundred and sixty-nine patients were included in this study, with ages ranging from 2 weeks to 84 years (mean 41 years). Gender analysis revealed a male predominance of 68% (n = 184) with females making up 32% (n = 85). There was no statistically significant difference in the age of males compared to females (p = 0.43). The most common age group of patients requiring a tracheotomy was patients > 50 years (n = 117; 43%), followed by the 35-49 year age group (n = 62; 23%). The majority of tracheotomies were done for upper airway obstruction (n = 220; 82%) and the rest for prolonged intubation (n = 49; 18%). The overwhelming majority of patients in the upper airway obstruction group had a head and neck tumour (n = 120; 56%), followed by airway stenosis (n = 40; 18%), head and neck sepsis (n = 24; 11%) and head and neck trauma (n = 22; 10%). Analysis of the age distribution for each diagnosis showed upper airway stenosis to be more common in the 1-15 year age group (n = 16; 40%). Patients with head and neck sepsis requiring a tracheotomy were mostly in the > 50 year age group (n = 8%) followed by the 16 34 year age group (n = 8%). Tracheotomies for prolonged intubation were most frequent in the age group between 35-49 years (n = 18%) followed by the > 50 year group (n = 11%). Trauma to the head and neck occurred most frequently in the 16-34 year age group (n = 11; 50%), followed by the 35-49 year age group (n = 6; 27%). Head and neck tumours formed the most common diagnosis and the affected age group was patients > 50 years (n = 88; 73%). A separate analysis of children younger than 16 years of age (n = 44) showed upper airway obstruction accounts for 70% (n = 31) and prolonged intubation 30% (n = 13) of the tracheotomies in children. The most common diagnosis in the upper airway obstruction group was airway stenosis (n = 19; 43%). Conclusion: Upper airway obstruction formed the overwhelming majority of the patients requiring a tracheotomy; this is in agreement with similar published studies from other African countries.(1,14,15,16) However, our data showed a higher percentage of tracheotomies performed as a result of prolonged intubation. The most common diagnosis for upper airway obstruction also differed with head and neck tumours found to be the most frequent, followed by head and neck sepsis and airway stenosis.(1,14,15,16
A Research Report (Neus7009) submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfillment of the requirement for the degree of Master of Medicine in Otorhinolaryngology (MFOSENTS60) Johannesburg 2018
Keywords: Tracheotomy